Evidence of Animal-Assisted Therapy in Neurological Diseases in Adults: A Systematic Review - Rodríguez-Martínez, María del Carmen; De la Plana Maestre, Alba; Armenta-Peinado, Juan Antonio; Barbancho-Fernández, Miguel Ángel; García-Casares, Natalia (MDPI, 2021)
Background: In recent years, the possibility of intervening humans with animal-assisted therapy (AAT) has been growing due to numerous physical, psychological, and social benefits provided to humanity, enabling them to maintain or improve their quality of life. There exist different animals through which this therapy can be performed. The purpose of this systematic review will focus on the effects of AAT in several neurological diseases. Methods: The search of clinical trials was carried out in the PubMed, Scielo, Embase and PEDro databases. The selection of articles was made according to the different inclusion and exclusion criteria, incorporating those that approached neurological diseases to be reviewed. Results: Twenty-five clinical trials were identified, seventeen of which were finally included in the review. The results indicate that animal-assisted therapy (AAT) in different neurological diseases has many benefits in several areas, for example, in motor and physical ability as well as in mental and behavioural health. Conclusions: This systematic review provides occupational therapy practitioners with evidence on the use of activity based on animal-assisted therapy as a novel field of intervention that can complement other therapies and obtain benefits in different populations.
Keywords: Animales - Uso terapéutico; Sistema nervioso - Enfermedades; Esclerosis múltiple; Alzheimer, Enfermedad de; Animal-assisted therapy; Neurological disease; Stroke; Multiple sclerosis; Dementia